SAT0050 A novel function of junctional adhesion molecule-C in regulation of trans-endothelial migration of murine synovial fibroblasts. (23rd January 2014) - Heitzmann, M.; Korb-Pap, A.; Wunrau, C.; Kollias, G.; Butz, S.; Vestweber, D.; Pavenstädt, H.; Pap, T.
Abstract : Background: Recent studies demonstrated the potential of rheumatoid arthritis fibroblast-like synoviocytes (RA-FLS) to emigrate from affected joints and migrate via the bloodstream toward distant healthy cartilage in the SCID mouse model of disease. While the mechanisms of breaking endothelial barriers by RA-FLS are largely unclear, the junctional adhesion molecule C (JAM-C) has become of interest in this context due to its involvement in trans-endothelial migration of leukocytes. Using the human TNF transgenic (hTNFtg) mouse as a model for human RA, we studied the role of JAM-C in the transmigration of FLS derived from these mice. Methods: The expression pattern of JAM-C on wild-type and hTNFtg FLS was analyzed by Western-blot and immunocytochemistry. We investigated the transmigratory capacity of these cells in a transmigration assay using murine endothelioma cells (bEnd.5) as an endothelial barrier, IL-1alpha treated murine cartilage tissue served as chemoattractant stimulus within this setting. Functional analyses included the knock down of JAM-C expression by siRNA against murine JAM-C as well as its neutralization by blocking antibodies. Results: The expression of JAM-C could be detected on the surface of both wild-type and hTNFtg FLS and it was primarly located on sites of cell-cell interactions. Additionally, Western blot data showed an elevated expression of JAM-C in FLS from hTNFtg mice. Our transmigration experiments demonstrated a markedly higher potential of hTNFtg FLS to migrate through the endothelial monolayer than FLS from wild-type mice (+40%, p≤0.05), and cartilage explants pre-treated with IL-1alpha as chemoattractant strengthened the migratory capacity of hTNFtg FLS. Interestingly, knock down of JAM-C expression on hTNFtg FLS mediated by siRNA decreased the number of transmigrated cells of about 40% comparing with mock control (p≤0.01). Equally, the neutralization of JAM-C by blocking antibodies against murine JAM-C resulted in a reduction of transmigration on a similar level. Conclusions: The inflammatory environment characteristic for joints of hTNFtg mice induces an up-regulation of JAM-C on FLS similar to that of human FLS during RA. Moreover, the differentiation of a trans-migrating phenotype of FLS, capable to break through endothelial barriers is supported by this environment. In this context, JAM-C seems to be contributed to this process of transmigration and, thus, to the extravasation of FLS and, therefore targeting JAM-C may be a promising therapeutic strategy for RA. Disclosure of Interest: None Declared